Fluid Learning with Arduino-Based on Engineering Design Process (EDP) to Improve Student's Problem Solving Ability - Ratih Eka Maryati; Anna Permanasari; Didit Ardianto (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
This study aims to obtain an overview of physics learning on the topic of fluid material with an Arduino-based engineering design process (EDP) to improve students' problem-solving abilities. This study used a quasi-experimental research method with a pretest-posttest control group design. The subjects in this study were students of class XI MIPA by taking two groups of subjects using a purposive sampling technique. The sample for the experimental class was 36 people and the control class was 36 people, so the total number of research subjects was 72 people. The learning implementation instrument was carried out using an observation sheet. The results of the ability to solve problems are measured using a description test which includes indicators of problem-solving abilities. Student responses using a Likert scale. The results of the data analysis showed that the average N-Gain achievement was in the medium category and the results of the independent test showed a significant difference in increasing problem-solving skills. Most of the students gave positive responses to learning with Arduino-based EDP, felt happy and motivated, provided benefits, every process undertaken by students provided challenges in solving the problems they faced so that fluid learning using the Arduino-based engineering design process (EDP) stages was able to improve students' ability to solve problems.